Investigation of alexithymia and levels of anxiety and depression among patients with restless legs syndrome - Yılmaz O (Dove Medical Press, 2018)
Onur Yilmaz,1 Yildizhan Şengül,2 Hakan Serdar Şengül,3 Fatma Büşra Parlakkaya,1 Ahmet Öztürk1 1Bezmialem Foundation University Medical Faculty, Department of Psychiatry, Istanbul, Turkey; 2Bezmialem Foundation University Medical Faculty, Department of Neurology, IIstanbul, Turkey; 3Gaziosmanpasa Taksim Research and Training Hospital, Department of Psychiatry, Istanbul, Turkey Purpose: The purpose of this study was to examine alexithymia among restless legs syndrome (RLS) patients, compare with healthy controls, and argue the clinical inferences of this relationship. We searched for anxiety and depression and their clinical outcomes among patients and searched whether the results are similar to previous studies. Patients and methods: Eighty-seven RLS patients and 88 age, gender, and educationally matched healthy controls were assessed in Bezmialem Foundation University Hospital. RLS patients and healthy controls were assessed with the Sociodemographic Data Form constructed for the present study, 20-item Toronto Alexithymia Scale (TAS-20), Beck Depression Inventory (BDI), and Beck Anxiety Scale (BAS). The patient group was also assessed with the International Restless Legs Syndrome Study Group (IRLSSG) RLS Severity Scale. Results: RLS patients were found to have greater TAS-20, BDI, and BAS scores compared with the control group (P < 0.05). RLS severity score was positively correlated with the scores of anxiety and depression scales. However, no significant relationship was found between scores of IRLSSG RLS scale and TAS-20 total and subscale scores. Conclusion: RLS patients were found to be more alexithymic than healthy controls, whereas no significant relationship was found between RLS severity and levels of alexithymia. Still, alexithymia might be a predictor for early diagnosis and may be considered in the treatment and follow-up of RLS. RLS patients have higher depression and anxiety scores than healthy individuals. Thus, depression and anxiety should be taken into consideration throughout the RLS treatment. Keywords: restless legs syndrome, alexithymia, anxiety, depression